Pengaruh Media Balok Kata Terhadap Kemampuan Literasi Baca Tulis Pada Anak Usia 5-6 Tahun - lailatul azzmil; Ervin Nurul Affrida (Universitas Muhammadiyah Metro, 2026)
Early literacy skills are an essential aspect of language development that should be stimulated during early childhood. However, preliminary observations at Bahrul Ulum Kindergarten, Surabaya, revealed that some children aged 5–6 years still experienced difficulties in recognizing letters, pronouncing syllables, and arranging letters into simple words. Although various studies have examined literacy learning media, the use of word blocks as a concrete manipulative medium to improve early literacy skills remains limited. Therefore, this study aimed to determine the effect of word block media on the literacy skills of children aged 5–6 years at Bahrul Ulum Kindergarten, Surabaya. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The participants consisted of 18 children aged 5–6 years. Data were collected through an observation sheet designed to assess literacy skills, including letter recognition, syllable pronunciation, and word formation abilities. The data were analyzed using a paired-sample t-test with the assistance of SPSS version 20. The results showed a significance value (Sig. 2-tailed) of 0.000, which is lower than 0.05, indicating that word block media had a significant effect on improving children's literacy skills. These findings demonstrate that word block media is effective in enhancing early literacy development by engaging children in concrete, interactive, and play-based learning activities. The implications of this study suggest that word block media can serve as an alternative instructional medium for early childhood educators to foster literacy development in a more enjoyable, meaningful, and developmentally appropriate manner